2023
DOI: 10.1101/2023.06.22.23291742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged grief during and beyond the pandemic: Factors associated with levels of grief in a four time-point longitudinal survey of people bereaved in the first year of the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has been a devastating and enduring mass-bereavement event, with uniquely difficult sets of circumstances experienced by people bereaved at this time. However, little is known about the long-term consequences of these experiences, including the prevalence of Prolonged Grief Disorder (PGD) and other conditions in pandemic-bereaved populations. Methods A longitudinal survey of people bereaved in the UK between 16 March 2020 and 2 January 2021, with data collected at baseline (n=7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…However, levels of death awareness are increasing and this has been attributed to amplified levels of consciousness and selfconsciousness in humans (Schumaker et al, 1991). Initial higher levels of death anxiety initially attributed to Covid-19 (Menzies & Menzies, 2020) are corroborated by subsequent empirical research, which illustrates the impact of social isolation and loneliness, resulting in poorer mental health outcomes in people with or without previous mental health problems (Menzies & Menzies, 2020;Harrop et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, levels of death awareness are increasing and this has been attributed to amplified levels of consciousness and selfconsciousness in humans (Schumaker et al, 1991). Initial higher levels of death anxiety initially attributed to Covid-19 (Menzies & Menzies, 2020) are corroborated by subsequent empirical research, which illustrates the impact of social isolation and loneliness, resulting in poorer mental health outcomes in people with or without previous mental health problems (Menzies & Menzies, 2020;Harrop et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Papers written prior to Covid-19 and subsequent briefing papers from early in the pandemic indicated that lockdowns in the United Kingdom were associated with mental health problems across the population, including prolonged grief disorder, post-traumatic stress, loneliness, and death anxiety (Menzies & Menzies, 2020;Selman et al, 2020;Hards et al, 2021). More recent research from a longitudinal study illustrates higher levels of prolonged grief disorder compared with pre-pandemic levels, which were influenced by social isolation, loneliness in early bereavement, and the absence of long-term social support (Harrop et al, 2023). In addition, risks of abuse and safeguarding issues related to children and young people (CYP) were also highlighted due to 'the pressure cooker of family life' (Green, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation